2016
DOI: 10.1136/archdischild-2016-310525
|View full text |Cite
|
Sign up to set email alerts
|

Eye-tracking-based assessment of cognitive function in low-resource settings

Abstract: BackgroundEarly development of neurocognitive functions in infants can be compromised by poverty, malnutrition and lack of adequate stimulation. Optimal management of neurodevelopmental problems in infants requires assessment tools that can be used early in life, and are objective and applicable across economic, cultural and educational settings.Objective and designThe present study examined the feasibility of infrared eye tracking as a novel and highly automated technique for assessing visual-orienting and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 26 publications
6
53
0
Order By: Relevance
“…The present study examined the development of visual attention capabilities in a large sample of infants living in rural settings in Malawi. Consistent with prior research in Western countries and a previous study in Malawi (Forssman et al., ), the results showed the predicted pattern of results at group level in tasks assessing visual search, anticipatory attention shifts, and attention to faces. The results also showed that there are changes in most of these measures between 7 and 9 months, consistent with the prediction that the measures are sensitive to development of visual attentional processes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study examined the development of visual attention capabilities in a large sample of infants living in rural settings in Malawi. Consistent with prior research in Western countries and a previous study in Malawi (Forssman et al., ), the results showed the predicted pattern of results at group level in tasks assessing visual search, anticipatory attention shifts, and attention to faces. The results also showed that there are changes in most of these measures between 7 and 9 months, consistent with the prediction that the measures are sensitive to development of visual attentional processes.…”
Section: Discussionsupporting
confidence: 91%
“…The non‐face‐patterns were created by phase‐scrambling the faces used in the experiment (see Peltola et al., for details). The faces were pictures of two Black females that had been tested in a small‐scale pilot study to look familiar to the local people and provide valid examples of the happy and fearful expressions (Forssman et al., ). The second stimulus was a geometric shape (black and white circles or a checkerboard pattern), which was superimposed by a still picture showing the first frame of a child‐friendly cartoon animation.…”
Section: Methodsmentioning
confidence: 99%
“…As did Forssman et al (2017) with Malawian infants using Tobii eye tacking instrumentation and a cognitive visual tracking task, we also established the feasibility of eye tracking measures with children in a medical clinic serving a disadvantaged rural Ugandan sample of at-risk children. We also established ways in which of ECVT eye tracking measures correlated to other cognitive and neurodevelopmental assessments in our study children.…”
Section: Discussionmentioning
confidence: 99%
“…However, we know of only one published report where Tobii eye tracking instrumentation has been used to evaluate neurocognitive response with children in the African setting. Forssman and colleagues (2017) presented a visual tracking and visual switching task to a sample of both Finnish (N=39) and Malawian (N=40) nine-month old infants in order to establish the feasibility of this sort of eye-tracking measure in a cross-cultural study (Forssman et al, 2017). Both groups of infants had a very high completion rate for the visual testing procedure while providing valid eye tracking data (> 90%), and parents in both cultures had a high acceptance rate of this kind of evaluation for their children.…”
mentioning
confidence: 99%
“…Forssman et al report the findings of a feasibility study that applied the same set of eye-tracking tasks, which were designed to evaluate social cognition and learning, to a group of infants from a high-income country (Finland) and a low-income country (Malawi) 8. The authors' motivation is clear: poverty and malnutrition are major determinants of neurodevelopmental impairment, so the burden of these problems is high in low-income countries.…”
mentioning
confidence: 99%